Atrocities on trial : historical perspectives on the politics of prosecuting war crimes - Heberer, Patricia (Univ. of Nebraska Press, 2008)
These essays are organised into four sections, dealing with the history of war crime trials from Weimar Germany to just after World War II, the sometimes diverging Allied attempts to come to terms with the Nazi concentration camp system, the ability of postwar societies to confront war crimes of the past and the legacy of war crime trials.